Can farmer collectives empower women and improve their welfare? Mixed methods evidence from India - Ray, Soumyajit; Raghunathan, Kalyani; Bhanjdeo, Arundhita; Heckert, Jessica (International Food Policy Research Institute, 2024)
Farmer Producer Organizations (FPOs)—farmer collectives, often legally registered - can mitigate some of the constraints smallholder farmers face by improving their access to extension, services, and markets, especially for women. We evaluate the effects of a set of interventions delivered through women-only FPOs in Jharkhand, India, using a panel of 1200 households and a difference-in-difference model with nearest neighbor matching. A complementary qualitative study in the same areas helps triangulate and interpret our findings. The interventions aimed to improve agricultural productivity by coordinating production and improving access to services, while also providing gender sensitization trainings to FPO leaders and members. We collect household data on asset ownership and agricultural outcomes and individual data on women’s and men’s empowerment using the project-level Women’s Empowerment in Agriculture Index for Market Inclusion (pro-WEAI+MI). Our results for asset ownership, land cultivated, cropping intensity, and per acre yields, revenues or costs are statistically insignificant. Effects on men’s and women's empowerment are mixed. While we see positive effects on women’s decisionmaking, asset ownership, control over income and attitudes towards intimate partner violence, the program is associated with an increase in workload and a reduction in active group membership for both men and women. Men appear to cede control over resources and decisionmaking to other household members. Additional analyses suggest that while some effects can occur in the short-term, others take time to accrue. FPO based interventions that aim to empower women or other marginalized groups likely require sustained investments over multiple years and will need to go beyond improving FPO functioning and increasing women’s participation to transforming social norms.